2021
DOI: 10.1109/tnsre.2021.3093006
|View full text |Cite
|
Sign up to set email alerts
|

A Full-State Robust Extended Kalman Filter for Orientation Tracking During Long-Duration Dynamic Tasks Using Magnetic and Inertial Measurement Units

Abstract: Accurate and robust orientation estimation using magnetic and inertial measurement units (MIMUs) has been a challenge for many years in long-duration measurements of joint angles and pedestrian dead-reckoning systems and has limited several real-world applications of MIMUs. Thus, this research aimed at developing a full-state Robust Extended Kalman Filter (REKF) for accurate and robust orientation tracking with MIMUs, particularly during long-duration dynamic tasks. First, we structured a novel EKF by includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
0
16
0
1
Order By: Relevance
“…The proprietary filter included with the sensors resulted in more drift for all subjects (Additional file 1 : Figure S5), likely because the filter rejected the distorted magnetometer signal over too long a duration. Recent work has shown that Kalman filters can be formulated to achieve good accuracy over long durations [ 24 ]. Some prior work has shown complementary filters drift with measurement duration [ 23 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proprietary filter included with the sensors resulted in more drift for all subjects (Additional file 1 : Figure S5), likely because the filter rejected the distorted magnetometer signal over too long a duration. Recent work has shown that Kalman filters can be formulated to achieve good accuracy over long durations [ 24 ]. Some prior work has shown complementary filters drift with measurement duration [ 23 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Validation studies applying sensor fusion methods in human movement analysis have reported average RMS differences in the range of 1.7°–8° for joint angles over short durations (on the order of one minute) [ 5 , 19 21 ]. Recent work has shown that sensor fusion algorithms [ 22 24 ] can produce estimations of sensor orientations with less than 10° RMS difference over five minutes. We extend the work by estimating drift-free physiologically realistic joint angles in new experimental conditions over 10 min.…”
Section: Introductionmentioning
confidence: 99%
“…EKFs are used for the sensor fusion of gyroscopes and accelerometers in order to estimate the joints orientation [8], [38], [66], [70], [72], [92], [96], joints orientation and location [55], [76], [79], [88], [108] and segment orientation [77], [78]. Researchers also use EKFs to fuse gyroscope and accelerometer data with magnetometer measurements to estimate the orientation of joints [138], [142] or segments [117], [118], [135], [140], [145]. EKFs are also combined with the Gauss-Newton algorithm to fuse the information of gyroscopes and accelerometers and estimate the orientation of joints [64].…”
Section: Adopted Algorithmsmentioning
confidence: 99%
“…Other corrections found in the literature that are not related with biomechanical properties include the following: modeling the bias of sensors or including them in the state vector [13], [19], [30], [33], [36], [44], [46], [52], [57], [60]- [63], [70], [75], [82], [83], [95], [117]- [119], [123], [125], [139], [153], [173]; calibrating this bias [30], [44], [46], [97], [104], [105], [121], [124], [133], [150]; low-pass filtering the recorded signals [11], [14], [37], [41], [45], [63], [71], [143], [145]; or optimizing them [67], updating the estimations when a direct observation of gravity is available or with its dynamic compensation [35], [43], [48],…”
Section: Adopted Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation